Population dynamics of the sea urchin Tripneustes gratilla (Linnaeus) (Echinodermata) in the seagrass beds of Southern Guimaras, Philippines, before and after the M/T Solar I oil spill - Regalado, Joshua Militar (University of the Philippines Visayas, 2015)
The sea urchin Tripneustes gratilla is a conspicious grazer found in the seagrass beds of Southern Guimaras, Philippines. In August 11, 2006, the M/T Solar I oil tanker sank 30 km south of Guimaras Island. The oil from the sunken tanker heavily impacted the coastal communities in Southern Guimaras. Post-spill sea urchin data were collected from surveys conducted in 2006-2012 under the UPV Oil Spill Response Program and was compared to pre spill data from 2000-2002. Overall sea urchin abundances from post-spill surveys (15.5 ind. *100m-2) were 76% lower compared to abundances from pre-spill survey (65.5 ind. *100m-2). This study examined population parameters from pre-spill and post-spill surveys to determine whether the reduction is due to the oil spill or natural fluctuation.This study shows that long-term data and sufficient base line information is necessary in examining the extent of variation and patterns in urchin population and in evaluating the impacts of low-frequency, non selective disturbances such as oil splls.